Transient Marangoni waves due to impulsive motion of a submerged body - Shu, Jian Jun (2011)
The Oseen problem in a viscous fluid is formulated for studying the transient free-surface and Marangoni waves generated by the impulsive motion of a submerged body beneath a surface with